Reading Strategies in Academic Communication (Based on the Harry Potter Series) - Pylynskyi, M.; Babushko, O. (Studia Philologica, 2021)
This article considers the correlation between reading strategies and peculiarities of academic discourse. Special attention is paid to the upbringing-educational potential of teaching English on the basis of selected materials, namely the seven-book series “Harry Potter” by Joan K. Rowling. The paper discusses a number of ways of sustaining the communicative focus of teaching a foreign language through the prism of a potential reading strategy. It is proved that the series authored by Joan K. Rowling is filled with modern lexical and phraseological means. Texts about Hogwarts magic and spells are exemplary among the works of modern English literary language, because it contains a wide range of thematic material of an instructive nature, which greatly contributes to both teaching and performing basic activities such as reading, speaking, writing, as well as critical thinking, text analysis and the formation of moral values. The study mentions multiculturalism in order to help students master the concept, as well as to realize that each unit of cultural diversity has the right and freedom to exist and respect it. The authors proved that Potterian material is rich in instructiveness and contains such topics as the influence of folklore on modern culture, multicultural manifestations, issues of freedom and slavery, raising “problem children” or interaction with non-biological parents and others. Specific techniques and strategies that are most appropriate for the treatment of the above topics are proposed. These can be text analysis, investigation and comparison of book’s world and modern life, as well as critical thinking. It is seen that effective communication is dialogue and group discussion, the amount of oral and written speech which must be balanced with quality. Key words: reading strategies, series of seven books, communication, educational potential, motivation, Joan K. Rowling, “Harry Potter”, multiculturalism.